Neuroscience and newspapers - Page, Graham (Henry Stewart Talks, 2010)
Myths about newspapers as advertising medium, complimentarity of TV and Newspapers, unique neuroscience research, TV/newspaper combination outperforms either alone, newspaper advertising builds brand emotion
Archived at 2022/11/27